2021
DOI: 10.1038/s41598-021-97320-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional fitness norms and trends of community-dwelling older adults in urban China

Abstract: This study aimed to (1) establish age- and sex-specific functional fitness (FF) norms in Chinese older adults living in urban communities and (2) explore ageing-related degradations and sex differences in each FF dimension. A pool of 2398 individuals (1128 men; 1270 women) aged 60–98 years were recruited from urban communities of Nanjing, China. FF was measured using the Senior Fitness Test battery. FF norms were established for men and women in 5-year age intervals using five percentiles (10th, 25th, 50th, 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…However, the decline rates in the different dimensions varied. The results showed that the flexibility of the upper and lower body declined most rapidly in women (236.0% and 114.2%) and upper body flexibility in men (483.3%), which were consistent with previous results in Nanjing (Zhao et al, 2021), HK (Chung et al, 2016), Portugal (Marques et al, 2014), and Poland (Ignasiak et al, 2020). Contrary to the information provided in Table 5, the report on Poland erroneously stated the following: The largest deficits involved the dynamic balance, with the reduction rate reaching 69% in men and 62% in women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the decline rates in the different dimensions varied. The results showed that the flexibility of the upper and lower body declined most rapidly in women (236.0% and 114.2%) and upper body flexibility in men (483.3%), which were consistent with previous results in Nanjing (Zhao et al, 2021), HK (Chung et al, 2016), Portugal (Marques et al, 2014), and Poland (Ignasiak et al, 2020). Contrary to the information provided in Table 5, the report on Poland erroneously stated the following: The largest deficits involved the dynamic balance, with the reduction rate reaching 69% in men and 62% in women.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies had investigated the normative values of functional fitness levels in Chinese (Chen et al, 2009;Wang, 2015;Chung et al, 2016;Lin, 2020;Zhao et al, 2021). However, the SFT integrated score is missing in nearly all published studies (Chen et al, 2009;Wang, 2015;Chung et al, 2016;Zhao et al, 2021), and some of these reports used different parameters with the SFT (Chen et al, 2009;Wang, 2015;Lin, 2020). In the present study, normative values of functional fitness Frontiers in Physiology frontiersin.org were established according to sex and age by using the data of SFT in 1,122 older adults in Suzhou, China.…”
Section: Discussionmentioning
confidence: 99%
“…Significant gender-related differences emerged only for flexibility and endurance. Fitness levels and coordination in the present study were in line with the literature for older individuals [ 36 , 43 , 44 ], whilst PCS and MCS achieved better results with respect to those reported in previous studies for older Italians [ 45 ]. The current study reinforces the added value of engaging in chronic sports training characterized by both aerobic-anaerobic and coordinative demands [ 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this sense, a reduction in functional fitness levels is generally associated with a decline in general functional capacity and basic activities of daily living such as climbing stairs, walking, carrying groceries, and many other common tasks [3,23]. Normative functional fitness scores have been published for older adults in different countries: United States of America [24]; Portugal [25]; Brazil [26]; Poland [27]; and China [28]. Results revealed a pattern of decline across most age groups on all variables.…”
Section: Functional Changes: Functional Fitness and Mobilitymentioning
confidence: 99%
“…The pattern of decrease over age was similar in men and women. However, men scored better on muscular strength, aerobic endurance, and agility/balance, and women scored better on flexibility [24][25][26][27][28]).…”
Section: Functional Changes: Functional Fitness and Mobilitymentioning
confidence: 99%